IMPLEMENTASI ELEARNING PADA MATA KULIAH FISIKA LINGKUNGAN UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DAN KEMANDIRIAN BELAJAR MAHASISWA - Anita Anita; Eka Trisianawati (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2016)
This study aims to determine how the implementation of elearning learning to critical thinking skills and independent learning on environmental physics. This research is descriptive research. Subjects in this study were students in environmental physics at IKIP PGRI Pontianak in 2015/2016. The techniques used in this study is documentation techniques, indirect communication, and measurement techniques. The result showed that the planning Elearning based APKG I is in excellent condition with a value of 3.25. Implementation of eLearning based APKG II is in excellent condition with a value of 3.40. Elearning evaluation based APKG II classified angat well with the value of 3.40. Critical thinking ability of students is low with an average value of 51.00. A total of 11 students have the ability to think critically low of 18 students. Student learning independence quite well with the percentage of positive answers and negative answers 72.78% 27.22%. Keywords: implementation, enviromental physics, e-learning, critical thiking skills, independent learning.